Drug reaction with eosinophilia and systemic symptoms (DRESS) and its relation with autoimmunity in a reference center in Mexico - Juan Manuel Ruiz Matta; Silvia Méndez Flores; Judith Domínguez Cherit (Sociedade Brasileira de Dermatologia, 2017)
Abstract: BACKGROUND: Drug reaction with eosinophilia and systemic symptoms is a severe adverse drug reaction, with a reported mortality of 10%. Long-term outcomes involve organic failure and autoimmune diseases in some populations. OBJECTIVE: To evaluate the clinical prognosis of patients with drug reaction with eosinophilia and systemic symptoms. METHODS: We conducted a retrospective review at a referral hospital in Mexico City in a period of 22 years (1992-2013), looking up for records with diagnosis of DRESS according to RegiSCAR criteria. Clinical characteristics, organ failures, culprit drugs, treatment, and short and long-term sequelae were analyzed. RESULTS: We found 11 patients with diagnosis of drug reaction with eosinophilia and systemic symptoms syndrome, 7 female and 4 male, with a median age of 22 years-old; 9 had maculopapular rash and 2 were erythrodermic. Affected organs were liver (8/11), kidney (6/11) and hematologic disorders (8/11). The most common culprit drugs were antiepileptic (63%). Systemic corticosteroids were given to 8 patients, being pyelonephritis (1/8) and pneumonia (2/8) the adverse events of this therapy. Long-term sequelae were 1 patient with renal failure, 1 patient with chronic anemia; and 2 patients developed autoimmune diseases (one autoimmune thyroid disease and another one with autoimmune thyroid disease and autoimmune hemolytic anemia). Study limitations: The retrospective nature of the study and the limited number of patients with drug reaction with eosinophilia and systemic symptoms. CONCLUSIONS: Drug reaction with eosinophilia and systemic symptoms syndrome has been linked to the development of chronic organ failure. We found two young patients who developed autoimmune diseases in the short term. Patients with drug reaction with eosinophilia and systemic symptoms should have a long-term monitoring for signs or symptoms suggestive of an autoimmune disease.